Single ray amputation in traumatic injury of the hand: review of literature - Calderazzi, Filippo; Menozzi, Margherita; Nosenzo, Alessandro; Galavotti, Cristina; Pogliacomi, Francesco; Ceccarelli, Francesco (Acta Biomedica Atenei Parmensis, 2018)
Background and aim of the work: ring avulsion are relatively common hand lesions and are associated with significant disability, especially in hand-workers. The treatment choice is still debatable. We sought to conduct a detailed systematic review in attempt to collate evidence on functional, cosmetic and patient-reported outcomes (PROs) following ray amputation for the management of traumatic hand injury and ring avulsion injury.Methods: using the PubMed database we made a systematic search for articles regarding single ray amputation after traumatic hand lesion. Nine articles met our including criteria and were analysed.Results: most of the included studies suggest that for those worse cases ray amputation still represent a good option. Indeed ray resection can eliminate the gap, remove a cumbersome or painful digit and guarantes better cosmesis but reduces grip and pinch strength (from 15% to 30%) and decreased palm width.Conclusions: different surgical techniques are available, almost all of them results in a loss of strength but ensure good both functional and cosmetic results.